Smart cities : foundations, principles, and applications - Song, Houbing; Srinivasan, Ravi; Sookoor, Tamim, 1984-; Jeschke, Sabina (John Wiley & Sons, 2017)
Addressing the various challenges and opportunities of creating smart cities and all that they have to offer, this welcome reference covers smart city theory modeling and simulation, and examines case studies of existing smart cities from all around the world. - Resumé vydavatel
Keywords: chytrá města; inovace; urbanismus; udržitelný rozvoj; životní prostředí měst; inteligentní dopravní systémy; smart cities; innovations; city planning; sustainable development; urban ecology; inteligent transport systems; elektronické knihy; sborníky; electronic books; papers of several authors